2022
DOI: 10.1109/ojap.2022.3206909
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Transparent Antennas: Advancements, Challenges, and Prospects

Abstract: Optically transparent electronic devices have attracted enormous interests in recent years. The development of transparent electronics emerges a lot of new industrial applications in variety of fields, such as displays, glasses, solar panels, satellite communications, terrestrial communications, integrated circuits, and sensors where optical transparency is required for unobtrusive placement of electronic devices on the surface. Over the last couple of years, there have been notable advancements in the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 97 publications
0
15
0
Order By: Relevance
“…Recently, the fabrication method and dielectric characteristics of the ceramic/polymer composite filaments for FDM of microwave devices (e.g., filters, antennas, and capacitors) have been widely investigated [ 154 , 155 , 156 , 157 , 193 ]. Castro et al [ 194 ] formulated two types of ceramic/polymer composite filament using polydimethylsiloxane (PDMS, which is a common substrate material for stretchable electronic devices [ 242 ], such as transparent antennas [ 243 ], field-effect transistors [ 244 ], photodetectors [ 245 ], and energy harvesters [ 246 ], because of its thermal stability, high optical transparency, and capability of attaining designer functionalities via surface modification and bulk property tailoring) reinforced by NdTi0 3 and MgCaTi0 2 fillers with volume loading up to 25%. After determining the microwave dielectric properties of the two types of ceramic/polymer composite filament, the authors demonstrated flexible microstrip antennas via an nScrypt 3Dn Tabletop printer coupling FDM and DIW.…”
Section: Applications Of Multi-materials 3d Printing In Functional Ce...mentioning
confidence: 99%
“…Recently, the fabrication method and dielectric characteristics of the ceramic/polymer composite filaments for FDM of microwave devices (e.g., filters, antennas, and capacitors) have been widely investigated [ 154 , 155 , 156 , 157 , 193 ]. Castro et al [ 194 ] formulated two types of ceramic/polymer composite filament using polydimethylsiloxane (PDMS, which is a common substrate material for stretchable electronic devices [ 242 ], such as transparent antennas [ 243 ], field-effect transistors [ 244 ], photodetectors [ 245 ], and energy harvesters [ 246 ], because of its thermal stability, high optical transparency, and capability of attaining designer functionalities via surface modification and bulk property tailoring) reinforced by NdTi0 3 and MgCaTi0 2 fillers with volume loading up to 25%. After determining the microwave dielectric properties of the two types of ceramic/polymer composite filament, the authors demonstrated flexible microstrip antennas via an nScrypt 3Dn Tabletop printer coupling FDM and DIW.…”
Section: Applications Of Multi-materials 3d Printing In Functional Ce...mentioning
confidence: 99%
“…Transparent antennas are visibly transparent devices that can transmit and receive electromagnetic (EM) signals. Since NASA proposed the first optically transparent microstrip patch antenna in 1997 [1], transparent antennas have experienced great development in the past two decades [2][3][4]. Because of the see-through feature, transparent antennas can be integrated onto solar panels, satellite, windscreens of automobiles, displays, windows, and so on [2][3][4], whose intrinsic performances are maintained without much degradation by the antennas.…”
Section: Introductionmentioning
confidence: 99%
“…Since NASA proposed the first optically transparent microstrip patch antenna in 1997 [1], transparent antennas have experienced great development in the past two decades [2][3][4]. Because of the see-through feature, transparent antennas can be integrated onto solar panels, satellite, windscreens of automobiles, displays, windows, and so on [2][3][4], whose intrinsic performances are maintained without much degradation by the antennas. Mechanical flexibility will endow transparent antennas with broader application scenarios, e.g., attachment onto curved surfaces and wearable devices, which however has not been investigated extensively [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Additional access points and signal repeaters embedded into the existing infrastructure help mitigate these issues through embedding transparent antennas into the windows by means of metallic meshes , /nanowires or transparent conductive oxides (TCOs). ,, The present article demonstrates the first TCO-based transparent antenna processed entirely by ALD. Optically transparent antennas based on both AZO and GZO have been previously demonstrated (comprehensive reviews on TCO-based antennas here ,, ). AZO antennas were fabricated to operate at 11 and 45 GHz, and a GZO antenna was fabricated to operate at 2.4 GHz.…”
Section: Introductionmentioning
confidence: 99%